Analysis of the Performances of Biogas-Fuelled Micro Gas Turbine Cogeneration Systems (MGT-CGSs) in Middle- and Small-Scale Sewage Treatment Plants: Comparison of Performances and Optimization of Mgts with Various Electrical Power Outputs - F., Basrawi; Takanobu, Yamada; Kimio, Nakanish; Hideaki, Katsumata (Elsevier Ltd., 2012)
The suitable size (electricity output capacity) of micro gas turbine cogeneration systems (MGT-CGSs) depending on scale of the sewage treatment plant was investigated. Since heat demand of the plant is affected by ambient temperature, performance under three typical ambient temperature conditions was investigated. Considering operation of the MGT-CGS under various loads and efficiency of the MGT-CGS under a partial load condition, the optimal combination of MGT-CGSs (MGT-Combination) with different sizes, 30 kW, 65 kW and 200 kW, was also proposed. An actual middle-scale plant was adopted as the analysis model, and it was scaled down to 0.50 and 0.25 in cases of smaller scale. Excluding MGT Combination, it was found that the MGT that has approximately the same fuel energy input under full load as the biogas energy produced in the plant has the highest efficiency. However, in the case of heat demand of the plant varying throughout the year such as the operation in a cold region, partial load operation will be frequent and efficiency will decrease. Furthermore, MGT-Combination has the highest efficiency but its efficiency will be the same as that of the other MGT-CGSs when only comparatively constant operation is required throughout the year such as operation in a tropical region.